Bridging disciplines with training in remote sensing for animal movement: an attendee perspective. Issue 1 (30th August 2016) - Clark, Bethany L.; Bevanda, Mirjana; Aspillaga, Eneko; Jørgensen, Nicolai H.
Abstract: Remote sensing and animal movement datasets are increasingly used to answer key questions in ecology and conservation. Collecting and accessing this data is becoming ever cheaper and easier, but limited analytical expertise limits its wider use. Working at the interface between these two disciplines is challenging as there are no standard techniques for handling the complex spatial data, so specific and in‐depth training is required. Higher education programs rarely cover remote sensing for animal movement, so external courses play a major role in training newcomers and creating a more unified global community. We conducted an online survey to investigate the views of previous attendees of four training courses that involve remote sensing and animal location data. These courses provided subject‐specific knowledge, practical and coding skills, networking, collaboration opportunities, insightful discussions and transferable research skills. Our survey highlighted the importance of real‐world examples, practical sessions, time for participants to work with their own data, preparatory material and open source software. Despite the value of interdisciplinary training in remote sensing and animal movement, it reaches few ecology and conservation practitioners outside of academia. We advocate more funding for underrepresented participants to attend existing course and the development of new courses. Abstract : Training courses in remote sensing and animal movement are rare, but play a major role advancing this interdisciplinary field. Our survey of previous participants revealed that courses are highly valuable in this field, but organizers and attendees face a number of challenges, and training is failing to reach ecology and conservation practitioners outside of academia. We provide a set of recommendations for prospective participants, course organizers and those making decisions on funding courses or attendance.